Racism in The Respectful Prostitute by Jean-Paul Sartre: Le racisme dans La putain respectueuse de Jean-Paul Sartre (Journal of the College of Languages (JCL), 2025)
Racism in the United States has been one of the most significant issues in society. As a committed existentialist French writer, Jean-Paul Sartre, tackles this issue in his play The Respectful Prostitute. This notable 20th-century literary work portrays racism in American society during that era. The main character, Lizzie, embodies American culture, which perpetuates racism, yet gradually learns to stand against it. On the other hand, Fred represents the extremist racists who never reject racism, thus prioritizing all citizens without exception, even criminals, at the expense of Black individuals, who are deemed guilty in any case. As for the Senator, he reflects the politicians who manipulate the American people and lead them toward racism through deceitful political slogans and false promises. Sartre’s work serves as an artistic masterpiece, unveiling the truth about society and refining it. It also advocates for the importance of freedom to liberate oneself from all feelings of hatred and racism.RésuméLe racisme aux Etats-Unis a été un fait marquant dans la société. Jean-Paul Sartre, en tant qu’écrivain engagé, s’en occupe en le dépeignant dans sa pièce La Putain respectueuse. Cette œuvre célèbre au XXe siècle expose sans détour les images du racisme dans la société à l’époque. Lizzie, l’un des personnages principaux, incarne la société américaine qui exerce le racisme, mais qui apprend peu à peu comment le dénoncer. Fred, de l’autre côté, représente les racistes extrêmes qui ne renoncent jamais, donnant le privilège à tout le monde, même les criminels, contre n’importe quel Noir, qui est considéré dans tous les cas comme coupable. Le Sénateur à son tour reflète la personnalité des politiciens qui manipulent le peuple, les guidant ainsi vers le racisme par de faux slogans et de fausses promesses. C’est donc un tableau sartrien qui démasque et réprimande la société, lui enseigne les valeurs de la liberté pour se libérer de tous les sentiments de haine et de racisme.